2021
DOI: 10.3390/foods10030527
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin Structure and pH Dependent Extraction Characteristics from Blueberries (Vaccinium corymbosum) and Chokeberries (Aronia melanocarpa) in Subcritical Water State

Abstract: This study determines the optimal extraction conditions for the subcritical-water extraction (SWE) of anthocyanin from blueberries and chokeberries and compares the performance using conventional extraction methods. SWE is carried out under different conditions of extraction temperature (110 °C, 130 °C, 150 °C, 170 °C, 190 °C, and 200 °C), extraction time (1, 3, 5, and 10 min), and solvent pH (water and 1% citric acid). The solubility and stability of anthocyanin from blueberries and chokeberries influences th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Their results demonstrated that the extraction efficient and the antioxidant activity of anthocyanin obtained from the raspberry by SWE were significantly higher than those obtained by conventional extraction with hot water or methanol [ 79 ]. Kang et al [ 80 ] also determined the optimal extraction conditions for extracting anthocyanins from blueberries and chokeberries by SWE. They optimized the temperature (110 °C, 130 °C, 150 °C, 170 °C, 190 °C, and 200 °C), the extraction time (1, 3, 5 and 10 min) and the pH of the solvent (water and 1% citric acid).…”
Section: Extraction Methods Used To Extract Anthocyaninsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results demonstrated that the extraction efficient and the antioxidant activity of anthocyanin obtained from the raspberry by SWE were significantly higher than those obtained by conventional extraction with hot water or methanol [ 79 ]. Kang et al [ 80 ] also determined the optimal extraction conditions for extracting anthocyanins from blueberries and chokeberries by SWE. They optimized the temperature (110 °C, 130 °C, 150 °C, 170 °C, 190 °C, and 200 °C), the extraction time (1, 3, 5 and 10 min) and the pH of the solvent (water and 1% citric acid).…”
Section: Extraction Methods Used To Extract Anthocyaninsmentioning
confidence: 99%
“…The total content of anthocyanins and the content of cyanidin-3-galactoside were three times higher in the extract obtained from chokeberries, when 1% of citric acid was used in the solvent. They also concluded that the solubility of anthocyanins depended on their structures; thus, the presence of more methoxy and hydroxyl functional groups in the basic skeleton of anthocyanin will result in a lower solubility [ 80 ].…”
Section: Extraction Methods Used To Extract Anthocyaninsmentioning
confidence: 99%
“…Thus, in an acidic environment, at pH = 1, anthocyanins are found in the form of the flavylium cation (red color) which makes them very soluble in water [ 12 ], and this form is also responsible for the production of red and purple colors. When the pH increases between 2–4, the quinoidal blue species is found abundantly, while at a pH between 5–6, carbinol pseudobase and a chalcone appear, compounds that are colorless [ 38 ]. Finally, at a pH higher than 7, the anthocyanins will be degraded according to the substituent groups.…”
Section: The Influence Of Phmentioning
confidence: 99%
“…This shows that the pH of water used for extraction can affect the TAC of the blue pea flower anthocyanin extract. Kang et al (2021) suggested that the reason for obtaining a higher extraction efficiency when using more acidic solvents is the higher stability shown by the anthocyanins in acidic medium. Some studies use a soaking step before extracting anthocyanins.…”
Section: Extraction Of Blue Pea Flower Anthocyaninsmentioning
confidence: 99%